746 COVID-19: Changing the Future of Emergency Epistaxis Management. (4th May 2021) - Devabalan, Y
Abstract: Introduction: Acute epistaxis can be a life-threatening airway emergency. Therefore, the majority of patients in whom conservative management (including cautery) has failed are admitted. However, due to the COVID-19 pandemic, our management has shifted towards a more outpatient centred approach. Method: A single centre retrospective study was undertaken of all epistaxis patients managed by the ENT team at our centre over a five-month period from 1 st January to 31 st May 2020. The first 10 weeks (Pre-COVID-19) were managed using pre-existing guidelines. The following 10 weeks (COVID-19) were managed using the new COVID-19 standard operating procedures which aimed to minimise inpatient admissions. Results: 142 patients, with similar demographic data, were seen across the 5-month period. There were significantly more patients aged over 65 presenting in the COVID-19 group (p = 0.04). There was a significantly increased use of local haemostatic agents (Nasopore ® and Surgiflo ®) and decreased use of nasal packing in the COVID-19 group. There were significantly fewer admissions (p < 0.0005) in the COVID-19 group, but similar rates of representation, length of stay and morbidity. Conclusions: The COVID-19 pandemic has accelerated the shift towards the use of local haemostatic agents and outpatient management of epistaxis, which is as safe and effective as previously well-established epistaxis management.